Electromagnetic flowmeter for dielectric liquids. - Amare, T. (Cranfield University, 1995)
Experimental investigation and theoretical analysis of an electromagnetic flowmeter designed for use with dielectric liquids has been carried out. An extensive survey of the industrial users of flowmeters has been made, involving the participation of over 47 companies, which provides information about the current industrial use, attitudes and attributes of electromagnetic and other types of flowmeters. The design of the flowmeter is mainly concerned with overcoming the charge noise that is associated with the flow of dielectric liquids so as to effectively detect the weak flow signal. It is shown that the working of the flowmeter depends heavily on the design of the eddy current free electrostatic shield. The result of the mathematical analysis of the design is a simplified formula for predicting the sensitivity of the meter. It is adjusted to take account of such factors as end-effects and electrical properties of the flow conduit of the meter. Experimental results show that not only an induction flowmeter based on Faraday's principle is possible but also the measured values of the flow signal closely matches those obtained from the formula. It is suggested that the formula can be generalised to include moderately conducting liquids which is supported by results achieved from experiments on water. Finally, recommendations for future work are put forward for further improvement of the design.